Interaction between atmospheric conditions and GPS accuracy: A case study from Istanbul - Eraslan, Ayça. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2019., 2019)
In this study, changes of the position data recorded by KANT permanent GPS station has been examined under the environmental conditions of the station. This cGPS station is situated in Kandilli Campus of Boğaziçi University and operated by Kandilli Observatory and Earthquake Research Institute. It is one of the sites of the Marmara GPS Network-MAGNET (TUBITAK), which was established for earthquake research in the Marmara Region. Data from KANT station has been continuously archived with thirty-second recording interval since 1999 in RINEX format. In this study, the position coordinates of the station have been obtained by GAMIT program with 2014 data. Data processing has been performed by selecting data from other short- and long-distance cGPS stations to minimize the potential errors and daily position GPS time series have been obtained. Error sources at such a permanent GPS station can be listed as satellite clock, upper atmosphere (ionosphere), receiver clock, satellite orbit, lower atmosphere (troposhere) and multipath. In this study, changes in the position coordinates of the station have been compared with atmospheric conditions to understand whether the effects of atmospheric pressure, temperature, wind and humidity. Meteorological data obtained from Meteorology Laboratory of the Institute in daily base. According to the results, the coordinate displacements caused by environmental conditions can be significant and the effects should be taken into account, especially in high-precision geophysical research.
Keywords: Atmospheric diffusion -- Mathematical models; Global Positioning System.